Prevalence of Potential Pathogenic and Antimicrobial Resistant Escherichia coli in Danish Broilers - Louise Ladefoged Poulsen; Magne Bisgaard; Henrik Christensen (MDPI AG, 2023)
Avian pathogenic Escherichia coli (APEC) are important bacteria in broiler production in terms of economy, welfare, and use of antibiotics. During a previous outbreak of APEC in the Nordic countries, it was suggested that the pathogenic clones of E. coli causing the outbreak originated from grandparent stock and were transmitted to the offspring, causing increased first week mortality. This study investigated whether the pathogenic potential of E. coli at the parent and broiler level differs in relation to pathogenic potential described by the level of virulence-associated genes and pattern of antimicrobial resistance. The hypothesis was that, due to higher biosecurity at the parent level, the E. coli population will show a lower level of antimicrobial resistance and carry fewer virulence-associated genes, as a result of fewer E. coli infections observed. From four parent flocks and eight broiler flocks, 715 E. coli were isolated from cloacal swabs of newly hatched chickens (Ross 308). The isolated E. coli were characterized by eight virulence-associated genes and phenotypic resistance against six antimicrobials. It was found that the prevalence of virulence-associated genes and phenotypic antimicrobial resistance varied significantly between flocks, and the virulence-associated genes papC and irp2 and resistance against ampicillin were significantly more prevalent in breeder flocks compared to broiler flocks.